Students' Thinking in Solving Integer Problems Based on APOS Theory in View of Gender - Putri, Nanda Azzahra; Subanji, Subanji; Sulandra, I Made (Universitas Suryakancana, 2025)
This research aims to describe the thinking of male and female students in solving whole number problems based on APOS theory. This descriptive qualitative research was conducted with two subjects, namely one subject with male gender and one subject with female gender. Both subjects are students with high mathematics ability. Subject selection was carried out using purposive sampling. Subjects were selected based on the scores obtained on the math problem test sheet. This research was conducted at one of the State Junior High Schools in Malang Regency. The instruments used in this study were math problem test sheets on integers and interviews. The results showed that: 1) Male students are able to fulfill all thinking indicators in each APOS mental structure in solving problems. Male students solve math problems through mental structures of action, process, object, and scheme; 2) Female students are able to fulfill all thinking indicators on each APOS mental structure in solving problems. Female students solve math problems through action, process, object and scheme mental structures.